Big data in multimodal medical imaging - El-Baz, Ayman S.; Suri, Jasjit S. (Boca Raton : CRC Press, 2020)
"There is an urgent need to develop and integrate new statistical, mathematical, visualization, and computational models with the ability to analyze Big Data in order to retrieve useful information to aid clinicians in accurately diagnosing and treating patients"--
Unique and important big-data radiomics features in multimodal medical imaging using machine learning techniques / Gengbo Liu, Youngho Seo, Debasis Mitra, and Benjamin L. Franc -- Multimodal medical image fusion in NSCT domain / Gaurav Bhatnagar, Zheng Liu and Q.M. Jonathan Wu -- Computer aided diagnosis in pre-clinical dementia : from single-modal metrics to multimodal fused methodologies / Yi Lao, Sinchai Tsao, Natasha Lepore -- Automated diagnosis and prediction in cardiovascular diseases using tomographic imaging / Lisa Duff, Charalampos Tsoumpas -- Big data in computational health informatics / Ruogu Fang, Yao Xiao, Jianqiao Tian, Samira Pouyanfar, Yimin Yang, Shu-Ching Chen, and S. S. Iyengar -- Fast dual optimization for medical image segmentation / Jing Yuan, Ismail Ben Ayed, Aaron Fenster -- Non-parametric bayesian estimation of rigid registration for multi-contrast data in big data analysis / Stathis Hadjidemetriou, Ismini Papageorgiou -- Multimodal analysis in biomedicine / Mohammad-Parsa Hosseini, Aaron Lau, Kost Elisevich, Hamid Soltanian-Zadeh -- Towards big data in acute renal rejection / Mohamed Shehata, Ahmed Shalaby, Ali Mahmoud, Mohammed Ghazal, Hassan Hajjdiab, Mohammed A. Badawy, Mohamed Abou El-Ghar, Ashraf Bakr, Amy C. Dwyer, Robert Keynton, Adel Elmaghraby, and Ayman El-Baz -- Overview of deep learning algorithms applied to medical images / Behnaz Abdollahi, Ayman El-Baz, Hermann B. Frieboes -- Big data in prostate cancer / Islam Reda, Ashraf Khalil, Mohammed Ghazal, Ahmed Shalaby, Mohammed Elmogy, Ahmed Aboulfotouh, Ali Mahmoud, Mohamed Abou El-Ghar, Ayman El-Baz -- Automatic detection of early signs of diabetic retinopathy based on feature fusion from OCT and OCTA scans / Nabila Eladawi, Ahmed ElTanboly, Mohammed Elmogy, Mohammed Ghazal, Ali Mahmoud, Ahmed Aboelfetouh, Alaa Riad, Magdi El-Azab, Jasjit S. Suri, Guruprasad Giridharan, and Ayman El-Baz -- Computer aided diagnosis system for early detection of diabetic retinopathy using OCT images / Ahmed ElTanboly, Ahmed Shalaby, Ali Mahmoud, Mohammed Ghazal, Andrew Switala, Fatma Taher, Jasjit S. Suri, Robert Keynton, and Ayman El-Baz.
OCLC-licensed vendor bibliographic record.
Keywords: Diagnostic imaging -- Data processing; Big data; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Database Management / Data Mining; COMPUTERS / Machine Theory